Die Begriffspaare von Urbild und Abbild, von Verstandeswelt und Sinnenwelt - Clemens Schwaiger (Lexicon Philosophicum)
A number of Platonic motifs that play a significant role in Kant’s thought already appear in Alexander Gottlieb Baumgarten’s Metaphysica, the decades-long guide to his lectures on this main philosophical discipline. This paper is the first to undertake a detailed analysis of the presumed sources of such Platonically-influenced key paragraphs from this work. According to § 866, God’s complete self-knowledge forms the unsurpassed model for a theology practised by finite beings. The classical distinction between ‘mundus sensibilis’ and ‘mundus intelligibilis’ takes on a decidedly practical flavour in § 869, when God is conceived of as the scrutinizer of hearts. In situating these two pieces of teaching historically, it becomes apparent that Baumgarten on the one hand draws on the conceptual pair of ‘theologia archetypa’ and ‘theologia ectypa’ common in the early modern period, and on the other hand on the final ethical-theological section of Leibniz’s Monadologie with its ideal conception of a moral world made possible by God.